As alterações da política agrária: um debate hermenêutico acerca da reforma agrária - Brasil, Luciangela Ferreira do (2019)
This master thesis, entitled "The changes in agrarian policy - a hermeneutical debate on agrarian reform", has as its central problem the following question: Does the Law 13.465 / 2017, breaks with the model of agrarian reform by implanting in Brazil from the Land Statute and with the precepts that were defined in the Constitution of 1988? Based on the observation that the Provisional Measure No. 759 issued by the federal government on December 23, 2016, has changed considerably the policy of urban and rural land regulation throughout the country. The aim of the work is to analyze how the Land Statute established the agrarian policy; the treatment given to the matter with its constitutionalization in 1988 and regulation through Laws 8.629 / 93 and 76/93; and the paradigmatic changes defined by Provisional Measure No. 759 converted into Law No. 13.465 / 2017. Using the methodology of bibliographical, exploratory and documentary research, it was analyzed the main norms of agrarian policy, defined by the State, through its legitimating role of the legal order.